Vascular Co-Option and Other Alternative Modalities of Growth of Tumor Vasculature in Glioblastoma - Ribatti, Domenico; Pezzella, Francesco (Frontiers in Oncology, 2022)
Non-angiogenic tumors grow in the absence of angiogenesis by two main mechanisms: cancer cells infiltrating and occupying the normal tissues to exploit pre-existing vessels (vascular co-option); the cancer cells themselves forms channels able to provide blood flow (the so called vasculogenic mimicry). In the original work on vascular co-option initiated by Francesco Pezzella, the non-angiogenic cancer cells were described as “exploiting” pre-existing vessels. Vascular co-option has been described in primary and secondary (metastatic) sites. Vascular co-option is defined as a process in which tumor cells interact with and exploit the pre-existing vasculature of the normal tissue in which they grow. As part of this process, cancer cells first migrate toward vessels of the primary tumor, or extravasate at a metastatic site and rest along the ab-luminal vascular surface. The second hallmark of vascular co-option is the interaction of cancer cells with the ab-luminal vascular surface. The first evidence for this was provided in a rat C6 glioblastoma model, showing that the initial tumor growth phase was not always avascular as these initial tumors can be vascularized by pre-existing vessels. The aim of this review article is to analyze together with vascular co-option, other alternative mode of vascularization occurring in GBM, including vasculogenic mimicry, angiotropism and trans-differentiation of glioblastoma stem cells.